30. NUTRITION STATUS AND QUALITY OF LIFE NON-SMALL CELL LUNG CANCER PATIENTS BEFORE CHEMOTHERAPY AT VIETNAM NATIONAL CANCER HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: To describe nutrition status and the quality of life non-small cell lung cancer patients before chemotherapy at Vietnam National Cancer Hospital.Materials and methods: A cross-sectional study was conducted on 95 patients with non-small cell lung cancer before chemotherapy at Vietnam National Cancer Hospital from January 2024 to November 2024.Results: According to PG-SGA, sixty percent of patients diagnosed with stage B and stage C. Average overall health score 70.88±23.47, average functional score 80.21±21.21, average symptom score 23.33±20.65 and financial burden score 27.37±35.39. Significantly, the patients under 60 years old had the lowest quality of life (p
Keywords: nutrition status; quality of life; non-small cell lung cancer; Viet Nam national cancer hospital